Surgical Critical Care Therapy A Clinically Oriented Practical Approach (Springer International Publishing, 2018)
This text provides a comprehensive, state-of-the art review of this field, and will serve as a valuable resource for clinicians, surgeons and researchers with an interest in surgical critical care. The book reviews up to date data regarding the management of common problems that arise in the Surgical Intensive Care Unit. The protocols, care bundles, guidelines and checklists that have been shown to improve process measures, and in certain circumstances, are discussed in detail. The text also discusses several well designed randomized prospective trials conducted recently that have altered the way we care for surgical patients with traumatic brain injury, hemorrhagic shock, acute respiratory distress syndrome, and sepsis. This book provides the practicing physician with a clinically oriented practical approach to handle basic and complex issues in the Surgical Intensive Care Unit. This text will serve as a very useful resource for physicians dealing with critically ill surgical patients. It provides a concise yet comprehensive summary of the current status of the field that will help guide patient management and stimulate investigative efforts. All chapters are written by experts in their fields and include the most up to date scientific and clinical information. This text will become an invaluable resource for all graduating fellows and practicing physicians who are taking the surgical critical care board examinations.